P237 Utility of diagnostic ultrasound in a rheumatology podiatry clinic. (20th April 2020) - Newcombe, Lisa; Tougher, John; Woodburn, James; Barn, Ruth
Abstract: Background: The use of musculoskeletal ultrasound (MSUS) is increasing with diagnostic, prognostic and treatment advantages for inflammatory disease. However, further work is required to determine its utility in podiatry clinics regarding diagnosis and management of lower limb pathology. The overall objective was to investigate the agreement between clinical and MSUS diagnoses and the impact of MSUS on treatment planning. Methods: Consecutive patients attending a rheumatology clinic at the Queen Elizabeth University Hospital Podiatry Department, Glasgow were invited to participate. Clinical diagnosis of foot problems and structures affected was conducted by a single experienced podiatrist (JT). MSUS assessment of affected structures was then conducted by a single podiatrist with US training (LN) using an Esaote MyLabAlpha portable US machine using two linear array transducers (IH6-18 and SL2325) with a range of 6-18MHz. Ultrasound findings were made available to the podiatrist responsible for diagnosis and management (JT) and any amendments to the diagnosis or treatment plan were recorded. Results: A total of 23 participants were recruited, 7 male and 16 female with a mean (SD) age of 54 (14) years. Across a range of pathologies, agreement between clinical examination and MSUS was 55% (Table 1). Where disagreement occurred, a range of additional findings were reported from MSUS including bursae, osteomyelitis, active inflammation (joint and tendon) and gout. MSUS assessment confirmed the treatment plan for 15 patients (65%) and altered the treatment plan for 8 patients (35%). The alterations included: 2 onward referrals for further imaging/antibiotic therapy; 4 rehabilitation programme adjustments (based on presence or absence of active inflammation); 2 orthotic plan adjustments; and 2 where corticosteroid injection was no longer indicated. Conclusion: When compared with an experienced clinician's clinical diagnosis of foot pathology, MSUS agreed in just over half of the cases. Additional diagnostic findings from MSUS were reported in 45% of the sample. One third of the management plans were amended due to MSUS findings. Further work is required in a larger sample, but these findings provide provisional evidence of the utility of MSUS for enhancing the accuracy of diagnosis and the tailored management of lower limb pathology in rheumatology. Disclosures: L. Newcombe None. J. Tougher None. J. Woodburn None. R. Barn None.